Tracing the Distribution of Late 16th and Early 17th Century European Copper Artefacts in Southern Québec and Ontario, Canada. (13th June 2017) - Pavlish, L. A.; Michelaki, K.; Moreau, J.‐F.; Farquhar, R. M.; Fox, W.; Anselmi, L. M.; Garrad, C.; Walker, C.; Warrick, G.; Knight, D.; Aufreiter, S.; Hancock, R. G. V.
Abstract : To understand the nature of trade/exchange of 'Basque' copper kettles and their fragments among Indigenous communities from Québec to Ontario, Canada, we examined 948 copper samples from 75 archaeological sites. We found that 936 samples were sortable into 11 coarse chemical groups: seven biased towards Ontario, three favouring Québec and only one balanced between the two provinces. This pattern may represent kettles and pieces 'mostly traded' or 'mostly kept' by Indigenous groups within Québec. Chemical group distribution within individual provinces is complex. A tentative chronology of copper chemical groups provides additional insight into the complex trading/exchange patterns among the Indigenous groups of southern Ontario.